Optimization of dosing methodof hybrid filler (Cellulose/MgAl LDH) in biopolymers using micro-compounder for preparation of bio-composites (2024)
With growing environmental concerns about using conventional plastics in daily life, the demand for bio-based polymer products is increasing. Natural and biodegradable raw materials are alternatives for making plastic products more sustainable. Cellulose-based fibers have gained attention in preparing biodegradable polymer composites because of their biodegradable nature, bio-based origin, low cost and low weight compared to synthetic fibers (glass and carbon). In this research, hybrid fillers based on cellulose and hydrotalcite were used in biodegradable polymers such as in PLA and blend of PBAT/PLA to prepare bio composites. The loading of hybrid filler (cellulose/LDH) was done using a small-scale compounding machine. Hybrid fillers were used in compounding machines in different forms (paste, freeze dried, PLA dissolved, PEG mixed, and sheet based) with PBAT/PLA. The dosing method of hybrid filler in polymer was optimized in this work. Morphological analysis of hybrid filler and the mechanical properties of bio composites were also done. The tensile modulus of PLA was increased by about 33% when sheet-based hybrid filler was added to the PLA composite.